Powdered activated carbon coupled with enhanced coagulation for natural organic matter removal and disinfection by-product control: Application in a Western Australian water treatment plant - Kristiana, Ina; Joll, Cynthia; Heitz, Anna (Elsevier, 2011)
The removal of organic precursors of disinfection by-products (DBPs), i.e. natural organic matter (NOM), prior to disinfection and distribution is considered as the most effective approach to minimise the formation of DBPs. This study investigated the impact of the addition of powdered activated carbon (PAC) to an enhanced coagulation treatment process at an existing water treatment plant on the efficiency of NOM removal, the disinfection behaviour of the treated water, and the water quality in the distribution system. This is the first comprehensive assessment of the efficacy of plant-scale application of PAC combined with enhanced coagulation on an Australian source water. As a result of the PAC addition, the removal of NOM improved by 70%, which led to a significant reduction (80–95%) in the formation of DBPs. The water quality in the distribution system also improved, indicated by lower concentrations of DBPs in the distribution system and better maintenance of disinfectant residual at the extremities of the distribution system.The efficacy of the PAC treatment for NOM removal was shown to be a function of the characteristics of the NOM and the quality of the source water, as well as the PAC dose. PAC treatment did not have the capacity to remove bromide ion, resulting in the formation of more brominated DBPs. Since brominated DBPs have been found to be more toxic than their chlorinated analogues, their preferential formation upon PAC addition must be considered, especially in source waters containing high concentrations of bromide.